Challenges and possibilities of the new High School from the perspective of teachers in a Public School (Research, Society and Development, 2023)
Law nº 13.415/2017 instituted the New Secondary Education and established certain formulations, such as, for example, the increase in the workload and curricular changes, bringing new challenges and possibilities to the school environment. With this, the objective of the study was to verify the challenges that the New High School is bringing to teachers, in addition to identifying which contents are most used to contextualize with the students' daily lives. The research has an experimental character, classified as qualitative in terms of approach. Data collection took place through an interview with 10 teachers, from March 13 to 15, 2023, where it was possible to make a verbal invitation to participate in the project and then sign the Free and Informed Consent Form. After data collection, the results were tabulated in the Excel 2013 program and transformed into graphs and tables. From the interview it was possible to identify that the teachers have a very varied age, ranging from 20 to 29 years old to 50 to 59 years old, it was also seen that the most used didactic resources were the textbook, magazines, posters, drawings and Datashow, since the most used contents to contextualize with the students' routine were genetics, anatomy, physiology and ecology. Thus, it was possible to identify the difficulties that teachers are experiencing due to the transformations that Secondary Education has been going through, and that the small amount of continuing education offered ends up leaving teachers insecure in the face of the new era of Secondary Education.